ANALYSIS OF THE SOCIOLECT INFLUENCE OF K-POPERS SLANG ON THE INDONESIAN LANGUAGE STANDARDIZATION OF UNISKA STUDENTS - Nuraini, Cut (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2025)
This study examines the influence of K-Popers slang, specifically among UNISKA students, on the standardization of the Indonesian language. Using a qualitative research approach, data was collected through in-depth interviews and content analysis of students’ online communication. The study found that K-Popers slang significantly impacts language use, particularly in informal settings, and poses challenges to the formal use of standard Indonesian. The use of slang terms such as “bias” and “stan” fosters group identity within the Carat fandom but reduces the students’ proficiency in formal language, which is critical in academic and professional contexts. This paper discusses the role of dakwah in addressing these challenges, suggesting that dakwah can guide students towards balancing informal and formal language use, promoting the preservation of standard Indonesian in line with religious and cultural values. The findings underscore the importance of incorporating dakwah in educational frameworks to maintain the integrity of language and ensure effective communication in both social and academic settings.